Feminist political theory : - Bryson, Valerie (Palgrave Macmillan, 1992)
Feminist Political Theory provides both a wide-ranging history of western feminist thought and a lucid analysis of contemporary debates. It offers an accessible and thought-provoking account of complex theories, which it relates to 'real-life' issues such as sexual violence, political representation and the family. This timely new edition has been thoroughly updated to incorporate the most recent developments in feminism and feminist scholarship throughout, in particular taking into account the impact of black and post-modern feminist thought on feminist political theory.